RESULTS OF EXPERIMENTAL RESEARCH OF THE MAIN COMPONENTS OF AUTOMATED INSTRUMENT SYSTEM STABILIZATION - BEZVESILNA, Olena; KOTLIAR, Svitlana; NECHAY, Serhii; ILCENKO, Mikola (Herald of Khmelnytskyi National University. Technical sciences, 2022)
This article presents the methodology and results of scientists conducted by the Department of Automation and Non-Destructive Testing Systems (ASNK) KPI. Igor Sikorsky and PJSC “RPA “Kyiv Automatic Plant”(KZA) experimental studies of the main components of the stabilizer of light armored vehicles (LAV). The purpose of experimental research is to measure on each of the motors of the stabilization system (SS) EDM20M, EDM02, EDM20 electromagnetic (τEL. MAGN.) And electromechanical time constants (τEL. MEX). Testing of engines according to the assessment of τEL. MAGN. were carried out as part of an automated instrument system for measuring mechanical quantities and stabilization and in an autonomous workplace for testing engines. When testing as part of the SS in the winding of the braked EDM20M (EDM02, EDM20) voltages were supplied from the amplifier of the engine control unit (ECU) level 27V. The feed time was limited to 20ms due to the use of technological time relay (TR) in the signal input circuit “SIGN. PWM "of the amplifier of the engine control unit. Simultaneously with the supply of this voltage, oscillography was performed: the voltage applied to the motor windings (to use this parameter as a reference) and the output voltage of the current sensor (UCS) of the ECU amplifier, which informs about the current in the winding. The current values were recalculated only for the maximum UCS values. The UCS oscillogram (increasing exponent) determined the time constant of the exponent, which corresponds to the electromagnetic time constant of the motor (excluding errors introduced by the inductances of the ECU chokes and power supply). When tested according to the autonomous scheme, the estimate τEL. MAGN. the engine was carried out according to the method, which is similar to the test method in the SS with the following differences: the voltage in the motor winding (hereinafter UPW) was applied at 2.4 V for ~ 25 ms; in the scheme of autonomous tests of engines the source of tension of a direct current B5-21, the switch 831140A 27B, technological R.Ch. to measure the EDM current consumed, a 75 mV × 50A shunt was installed in series in the motor winding. According to the results of experiments, the following main technical characteristics are established. Electromagnetic time constants are: 0.7 ms - for EDM20M; 0.7 ms - for EDM02; 0.85 ms - for EDM20. Electromechanical time constants are: 20 ms - for EDM20M; 24 ms - for EDM02; 26 ms - for EDM20.
Keywords: arm stabilizer; light armored vehicles; engine; stabilization systems